Penyuluhan Budidaya Ikan Lele dalam Drum di Pekarangan Rumah untuk Meningkatkan Ketahanan Gizi Keluarga pada Masa Pandemi Covid-19 - Hendar Nuryaman; Djuliansah, Dedi; Cahrial, Eri; Apriani, Dwi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this community service program is to provide counseling on catfish cultivation in the yard by using a drum. The catfish that are kept are expected to become food reserves, so that they can increase the nutritional security of the family. For partners who are interested in pursuing commercial catfish cultivation skills, there is the possibility of becoming a source of side income in this Covid-19 pandemic era. The method used is learning by doing counseling through lectures/discussions, practice and demonstrations. The results of activities can be reported, carried out according to the plan. There is a transformation of knowledge and skills. Partners are able to carry out catfish farming to strengthen family nutrition. Some of the partners are interested in cultivating catfish for commercial purposes. However, in terms of the implementation time of this service program, it has not been realized. Conclusion a. Increased knowledge and skills of partners in catfish farming; b Availability of protein sources to strengthen family food nutrition security; c. The creation of business opportunities for those who are interested in managing catfish farming on narrow land commercially.